1995
DOI: 10.1111/j.1744-313x.1995.tb00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Patterns of Hla‐dr Antigen Expression in Normal Epithelium, Hyperplastic and Neoplastic Malignant Lesions of the Breast

Abstract: Fifteen samples of non-tumoural breast tissue, 24 cases of benign lesions, four biopsies of inflammatory carcinomas and 94 tumour samples of primitive mammary carcinomas were analysed for HLA class II expression. We found, first, that HLA class II antigens were detectable in all cases of non-neoplastic breast tissue. Secondly, HLA class II antigen expression was notably increased in benign neoplasms and hyperplastic lesions. In contrast, only 32 out of 94 carcinomas showed expression of HLA-DR antigens, 17 tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Many studies have showed that MHC-class II antigens play a role in progression of malignant tumors via immunologic modification. [26][27][28][29][30][31] Our current results were consistent with their results. In this regard, our finding is not a new one.…”
Section: Discussionsupporting
confidence: 83%
“…Many studies have showed that MHC-class II antigens play a role in progression of malignant tumors via immunologic modification. [26][27][28][29][30][31] Our current results were consistent with their results. In this regard, our finding is not a new one.…”
Section: Discussionsupporting
confidence: 83%
“…12 The frequency of these changes varies among the different types of hematopoietic and solid tumors depending on their origin and/or molecular phenotype 23,30,31 : for example, more than 80% of ductal breast carcinoma lesions analyzed lack HLA class II antigen expression. 29,30 In contrast, about 50% of papillary thyroid carcinoma and 60% of primary melanoma express HLA class II antigens 31,32 suggesting a gain of HLA class II antigen expression in these tumor types. In addition, a heterogeneous intra-tumoral HLA class II antigen expression pattern was detected in HLA class II antigen-positive tumor lesions.…”
Section: Expression Of Hla Class II Antigens In Malignant Tumorsmentioning
confidence: 99%
“…13,14 However, the significance of these findings is controversial as some studies suggested DR expression on breast tumor cells is associated with favorable prognostic indicators such as well-differentiated tumors 15,16 and hormone receptor expression, 17 while others found no effect. 13,18 Similarly, tumor cell DR was positively associated with T-cell infiltration in some studies 19,20 and unrelated in others.…”
mentioning
confidence: 99%
“…13,18 Similarly, tumor cell DR was positively associated with T-cell infiltration in some studies 19,20 and unrelated in others. 16,21 Interpretation of the above studies may have been hampered by the fact that generic and not allelic DR expression was examined. This was likely because of the paucity of allotype-specific antibodies and the large number of DRB1 alleles, most of which are in linkage with additional structural DRB genes.…”
mentioning
confidence: 99%